Astana economic forum as a special economic phenomenon - Tatarkin, A. (Ye.A.Buketov Karaganda State University Publ., 2014)
It is noted that the main organizer of the Astana Economic Forum is the «Eurasian economic club of scientists » Association. It is emphasized that during the existence this forum has taken place as an effective dialogue platform for expression of modern scientific thoughts. Reasonable arguments for benefit of appeal of this economic forum are given. It is proved that Astana forum — a new horizons and possibilities of crossborder cooperation between Kazakhstan and Russia. It is concluded that the agendas of the Astana forum are focused on key strategic directions of development of our planet economy. The contribution of Russian scientists in developing specific actions related to the challenges and prospects of further development of the global economy.
Астана экономикалық форумы айрықша экономикалық құбылыс ретінде
Астанинский экономический форум как особое экономическое явление
Keywords: forum; integration; world society; cooperation; economy; joint projects; strategy; formation